Análisis de la gestión operativa en la dirección de emprendimiento y fortalecimiento económico del gad de quevedo, primer semestre 2024 - Rodríguez Pacheco, D Alember Jamil (2025)
The general objective of this paper was to analyze operational management in the Directorate of Entrepreneurship and Economic Strengthening of the Decentralized Autonomous Government (GAD) of Quevedo during the first half of 2024. To this end, a methodology based on descriptive and exploratory research was employed, using inductive, deductive, and analytical methods. The population consisted of 17 officials from the Directorate and 324 entrepreneurs selected from a total of 2,045 SMEs registered in the canton. Techniques such as interviews, surveys, and document review were used, while the applied instruments included observation guides and questionnaires. The results showed that operational management presents several limitations. Problems in strategic planning were identified, affecting the efficient execution of entrepreneurship programs. Insufficient resource allocation hampers the implementation of initiatives and support for entrepreneurs. Furthermore, the lack of clear administrative processes and limited staff training impact the quality of service and the guidance provided to beneficiaries. It was also observed that program dissemination is poor, limiting entrepreneurs' access to financing and training opportunities. In conclusion, it is necessary to strengthen planning, improve resource allocation, and establish monitoring and evaluation mechanisms to optimize operational management and ensure a greater impact on Quevedo's entrepreneurial ecosystem